CSCEC : transformation and development - McFarlan, F. Warren (SAGE knowledge. Cases., 2016)
In his report to the 2010 annual meeting of CSCEC (China State Construction Engineering Corporation), Mr Jun Yi, President, CEO & CPC Secretary of the giant SOE (state-owned enterprise) and one of the biggest construction corporation in China, expressed deep satisfaction with the company's achievements during the '11th Five-Year Program' period (2006-2010). He was especially pleased with 2010, the first full year after the world economic recovery from the global financial crisis in 2008 and the company's IPO in 2009. In 2010, CSCEC's new contract value, business revenue, and total profit increased by 74.5%, 42.3%, and 47.5%, respectively. This case study examines this topic.